Fletch [videorecording (DVD)] - Ritchie, Michael, 1938-2001; Chase, Chevy; Matheson, Tim, 1947-; Mcdonald, Gregory, 1937-2008 (Universal Home Video, 1998)
While working on a drug expose, investigative reporter Irwin Fletch attracts the attention of a strange businessman. The wily Fletch senses a scam and soon he's up to his byline in frameups, murder, police corruption and forbidden romance. It'll be the story of the year, if he can stay alive to meet his deadline.